2017
DOI: 10.1016/j.ejmech.2017.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and pro-apoptotic activities of 2′- and 4′-aminochalcones against tumor canine cells

Abstract: In the present study, a series of 2'- and 4'-aminochalcones were synthesized and their antiproliferative activity against a canine malignant histiocytic cell line (DH82) was evaluated. Particularly aminochalcones with a hydrophobic substituent on ring B proved to be potent antiproliferative agents. Among these compounds, aminochalcones 3, 4 and 11 inhibited the growth of DH82 cells, with IC values of 34.4, 31.4 and 38.2 μM, respectively, and were three times more potent than etoposide (IC = 95.5 μM). The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
(33 reference statements)
0
30
0
Order By: Relevance
“…Statistical analyses were carried out using one-way ANOVA multiple comparison tests followed by Tukey's HSD test 19,27 . Statistical significance difference was considered if p< 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analyses were carried out using one-way ANOVA multiple comparison tests followed by Tukey's HSD test 19,27 . Statistical significance difference was considered if p< 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Reagents and solvents were purchased from Merck V R (Kenilworth, NJ). Series of 20 chalcones was synthesised by Claisen-Schmidt aldol condensation reaction, according to protocol described by Santos and coauthors, with minor modifications 19,20 . Reactions were carried out at room temperature using 3.0 mmol of 4'-aminoacetophenone and 3.0 mmol of aldehydes, which were dissolved in ethanol (30 mL).…”
Section: Chemical Procedures For Synthesis Of Chalcones 1-20mentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has been working to identify small molecules that can be used as metastasis inhibitors through the induction of p53 [ 12 , 13 ]. Prominent among these are chalcones, a group of polyphenolic compounds with an alpha-beta unsaturated ketone core moiety that exerts cytotoxic activity against different tumor cell lines through mechanisms such as cell cycle disruption, the inhibition of angiogenesis, and the induction of apoptosis [ 14 , 15 , 16 , 17 ]. In previous works using U2OS osteosarcoma cells and other tumor cell lines, we found that trans-chalcone has apoptotic activity mediated by p53 activation, in addition to regulating genes involved in cell migration and invasion [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of BC1 was achieved by the reaction between acetovanillone (5 mmol) and benzaldehyde (5 mmol) at room temperature using ethanol as the solvent and ethanolic solution of NaOH (1.0 mol/L, 5 mL), using a protocol reported by Santos and collaborators with minor modifications [ 31 ]. The reaction mixture was stirred and monitored by successive thin-layer chromatography (TLC) analyses.…”
Section: Methodsmentioning
confidence: 99%